(untitled) - Institut National de la Recherche Agronomique (INRA) (Paris, 1993)
Aquaculture is a growing industry. A vital component of the subject is feeding the organisms under cultivation. This book provides a thorough review of the scientific basis and applied aspects of fish nutrition in a user-friendly format. It will be of great use to individuals working or training in the industry, and to fish feed manufacturing personnel.
Keywords: Fishes,Fishes; Nutrition,Feeds and feeding